Assessing the anti-fungal efficiency of filters coated with zinc oxide nanoparticles. Issue 5 (3rd May 2017) - Decelis, Stephen; Sardella, Davide; Triganza, Thomas; Brincat, Jean-Pierre; Gatt, Ruben; Valdramidis, Vasilis P.
Abstract : Air filters support fungal growth, leading to generation of conidia and volatile organic compounds, causing allergies, infections and food spoilage. Filters that inhibit fungi are therefore necessary. Zinc oxide (ZnO) nanoparticles have anti-fungal properties and therefore are good candidates for inhibiting growth. Two concentrations (0.012 M and 0.12 M) were used to coat two types of filters (melt-blown and needle-punched) for three different periods (0.5, 5 and 50 min). Rhizopus stolonifer and Penicillium expansum isolated from spoiled pears were used as test organisms. Conidial suspensions of 10 5 to 10 3 spores ml −1 were prepared in Sabouraud dextrose agar at 50°C, and a modified slide-culture technique was used to test the anti-fungal properties of the filters. Penicillium expansum was the more sensitive organism, with inhibition at 0.012 M at only 0.5 min coating time on the needle-punched filter. The longer the coating time, the more effective inhibition was for both organisms. Furthermore, it was also determined that the coating process had only a slight effect on the Young's Moduli of the needle-punched filters, while the Young's Moduli of the melt-blown filters is more susceptible to the coating method. This work contributes to the assessment of the efficacy of filter coating with ZnO nanopaticles aimed at inhibiting fungal growth.